Teori Konstruktivisme dalam Pembelajaran - Suparlan Suparlan (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
The task for education is not only limited to diverting the results of science and technology. In addition, the education sector has the duty to instill new values demanded by the development of science and technology in students within the framework of the basic values agreed upon by the Indonesian people. In general, the theory is a number of syntactically integrated proposals (these propositions follow rules that can logically link one proposal to another, and also to the observed data), as well as those used to predict and explain events. observed. Constivism is an active activity, where students develop their own knowledge, look for the meaning of what they are learning, and are a process of completing new concepts and ideas with their existing framework of thinking.